Prosedur Pelaporan PPh Pasal 21 Atas Karyawan Tetap Pada Kantor Pertanahan Kabupaten Banyuwangi Melalui Sistem CoreTax - Hizkia Joan Pracondo (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
Reporting Income Tax Article 21 for permanent employes is mandatory for all permanent staff working in an institution. Income Tax Article 21 plays an important role in the development of the country as it is one of the largest state revenues in taxation in Indonesia. In the implementation of this Field Work Practice, the aim is to understand the Procedure for Reporting Article 21 Income Tax for Permanent Employes at the Banyuwangi Regency Land Office Thru the CoreTax System. The data collection techniques in this Field Work Practice Report include observation, interviews, and literature study. The type of data in this report is quantitative and qualitative data. Using primary and secondary data sources. The Conclusion is The Procedure for Reporting Article 21 Income Tax for permanent employes thru the coretax system is a new development in the field of taxation, especially at the Banyuwangi District Land Office. Individual Taxpayers can independently report their Annual Tax Return thru the CoreTax system by providing the withholding tax certificate issued by the previous institution. With the withholding tax certificate obtained from that institution, individual taxpayers can report thru the CoreTax system when the reporting time arrives. Once the reporting is completed, individual taxpayers will receive a receipt that can be kept as an archive to be used if there is any administrative need.
:: Finalisasi file repositori 16 Juli 2026_Kurnadi
Keywords: Tax; Income Tax Article 21; CoreTax